Pengaruh Job Insecurity, Faktor Anteseden, dan Konsekuensinya terhadap Keinginan Berpindah Karyawan: Studi Empiris pada Kantor Akuntan Publik di Indonesia - Vince Ratnawati; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to determine the effects of job insecurity on turnover intention.  In particular, this study examines the effects of job insecurity, its antecedents factors (such as job satisfaction, role conflict, and locus of control), and its consequence (such as organizational commitment) on turnover intention.The data are collected through mail survey from ninety-eight auditors from a sample of CPA firms. Six variables are investigated in this study.  Those are job satisfaction, role conflict, locus of control, job insecurity, organizational commitment, and turnover intention.The results show that role conflict and locus of are antesedent of  job insecurity and organizational commitment is a consequence of job insecurity. The results also show job satisfaction directly affects organizational commitment and that organizational commitment and role conflict directly affect  turnover intention.  Thus, the effort to decrease the turnover intention is carried out by reducing role conflict and job insecurity level, and increasing internal locus of control and organizational commitment.